Comparing conVEntional RadioTherapy with stereotactIC body radiotherapy in patients with spinAL metastases: study protocol for an randomized controlled trial following the cohort multiple randomized controlled trial design. Issue 1 (December 2016) - van der Velden, Joanne; Verkooijen, Helena; Seravalli, Enrica; Hes, Jochem; Gerlich, A.; Kasperts, Nicolien; Eppinga, Wietse; Verlaan, Jorrit-Jan; van Vulpen, Marco
Abstract Background Standard radiotherapy is the treatment of first choice in patients with symptomatic spinal metastases, but is only moderately effective. Stereotactic body radiation therapy is increasingly used to treat spinal metastases, without randomized evidence of superiority over standard radiotherapy. The VERTICAL study aims to quantify the effect of stereotactic radiation therapy in patients with metastatic spinal disease. Methods/design This study follows the 'cohort multiple Randomized Controlled Trial' design. The VERTICAL study is conducted within the PRESENT cohort. In PRESENT, all patients with bone metastases referred for radiation therapy are enrolled. For each patient, clinical and patient-reported outcomes are captured at baseline and at regular intervals during follow-up. In addition, patients give informed consent to be offered experimental interventions. Within PRESENT, 110 patients are identified as a sub cohort of eligible patients (i.e. patients with unirradiated painful, mechanically stable spinal metastases who are able to undergo stereotactic radiation therapy). After a protocol amendment, also patients with non-spinal bony metastases are eligible. From the sub cohort, a random selection of patients is offered stereotactic radiation therapy (n = 55), which patients may accept or refuse. Only patients accepting stereotactic radiation therapy sign informed consent for the VERTICAL trial. Non-selected patients (n = 55) receive standard radiotherapy, and are not aware of them serving as controls. Primary endpoint is pain response after three months. Data will be analyzed by intention to treat, complemented by instrumental variable analysis in case of substantial refusal of the stereotactic radiation therapy in the intervention arm. Discussion This study is designed to quantify the treatment response after (stereotactic) radiation therapy in patients with symptomatic spinal metastases. This is the first randomized study in palliative care following the cohort multiple Randomized Controlled Trial design. This design addresses common difficulties associated with classic pragmatic randomized controlled trials, such as disappointment bias in patients allocated to the control arm, slow recruitment, and poor generalizability. Trial registration The Netherlands Trials Register number NL49316.041.14. ClinicalTrials.gov registration numberNCT02364115 . Date of trial registration February 1, 2015.